An unusual case of nasopharyngeal carcinoma (Bangladesh Journal of Otorhinolaryngology, 2012)
Though rare in other parts of the world, nasopharyngeal carcinoma (NPC) is relatively rare in Eastern and Southeast Asia (18% of all malignant tumours). Nonetheless spindle cell type of NPC is extremely rare all over the world. Ophthalmo-neurologic manifestations of nasopharyngeal carcinoma are also very rare. Here we present a case of spindle cell type of nasopharyngeal carcinoma with ophthalmo-neurological and cutaneous manifestations. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12028 Bangladesh J Otorhinolaryngol 2012; 18(2): 225-230